"Cicero the philosopher at work: the genesis of De Officiis III" - Gilbert, Nathan (Cambridge University Press, 2023)
In the chapter I argue that we should set aside the Quellenforschung arguments of Lefèvre and Brunt and Atkins and others and look at what Cicero is up to in book 3, where he aims to fill in a gap left by Panaetius and not followed up by Posidonius. My analysis focuses in particular on Cicero’s redeployment of the Ring of Gyges thought experiment to undercut the Epicurean reliance on Kuria Doxa (KD) 5 to bolster their ‘moral’ hedonism; and the critical role, or so I argue, of the correspondence with Cassius (which cites KD 5 in Fam 15.19) in the development of Cicero’s argument (with additional reference to Fin. 1-2, where KD 5 also takes a critical role). In addition to making the case for the importance of the correspondence as ‘work in progress’, I argue that Cicero’s engagement with Posidonius, Panaetius et al. represents a mature, confident Cicero philosophus, ready to make a targeted contribution to Stoic ethics, with none of the dissimulatio doctrinae of the works of the 50s.
EPrint Processing Status: Full text deposited in DRO